Using Work Sampling Method to Calculate Raw Time and Production Capacity of Roll Pallets at PT. Xyz - Banyu Faidz Musthafa Taqwatullah; Asep Erik Nugraha (International Journal of Education, Information Technology, and Others, 2022)
This study aims to determine the standard time required in one cycle of pallet roll production work so that the production capacity can be known. In this study, the work sampling method was used to calculate the standard time, and an objective method was used to determine the adjustment factor. There are several steps to obtain the standard time from a soap chip sack work cycle, namely: conducting preliminary measurements, testing data uniformity, testing data adequacy, determining adjustment factors, determining allowance factors, and calculating cycle times and normal times. From the calculation results, the standard time needed to work on pallet rolls for 7 days is 0.1165 minutes/pcs, or the equivalent of 6.99 seconds/pcs. So that the production capacity that can be produced depends on the number of hours on the existing shift. For shifts I and II with a total of 7 hours of work, the capacity can reach 3605 pallets. As for shift III with a total of 6 hours of work, the capacity can reach 3090 pallets